Media Usage Patterns: A Study on the People of Southwestern Part of Bangladesh - Rashid, Mamunor; Hossain, Sara Monami; Kabir, Md. Ripul (South Asian Journal of Social Sciences and Humanities, 2022)
The media, which is a potent social system, has a significant impact on how people see  reality. The idea that, in a broader cultural sense, the media mostly supported those values  and standards that had already attained a broad consensus base, proved to be significant.  People in Bangladesh's southwest use a variety of media to gather information. The objective  of the study is to find out the pattern of media user in the southwestern part of Bangladesh.  Uses and Gratification theory is used here, and a quantitative survey research design were used for this research. The study area includes the four districts of Bangladesh- Khulna,  Jashore, Satkhira, and Bagerhat. Purposive and snowball sampling is used for this study. A  standardized questionnaire was used to collect the data. Then the collected data are entered  into the descriptive statistics module of SPSS using tools like tables, frequency counts, and  simple. People in Bangladesh's southern region continue to consider that traditional media,  such as television and newspapers, are more trustworthy information sources than social  media or online portal. Due to their ample free time, the majority of adults consume media in  the evening. Although it appears on the surface that the majority of people in Bangladesh's  southern region utilize media for enjoyment, the reality is quite different. Major respondents  concur that they are impacted by media. They think that biased information has been  provided by the media. Also, according to the data, majority believes that local media  coverage is insufficient.
Keywords: Media; Pattern; People; Southwestern Region; Bangladesh